"Seikatsu Rinsho" – a values-based approach to supporting recovery in Japan. Issue 3 (24th June 2021) - Iseda, Takashi; Ogawa, Kazuo; Hasegawa, Kenichi; Yamasaki, Syudo; Nishida, Atsushi; Shepherd, Geoff
Abstract : Purpose: This paper aims to introduce Seikatsu Rinsho, a values-based approach to supporting recovery based on identifying service user values and aspirations that have been developed since 1958 in Japan where mental health services are still hospital-based and user involvement is not well-developed. This paper believes this will be of great implications for future practices around the world. Design/methodology/approach: Hope is essential to recovery and that hope is dependent on identifying what service users really want for themselves (aspirations) and then ensuring that these are communicated to – and supported by – professionals and carers. This is achieved through examining the life events, which are likely to trigger relapse for a specific individual, the important choices that the person has made throughout his/her life course and the reasons behind them. Through a process of "co-production", an attempt is made to understand the values expressed in these choices in the context of family history over several generations. Findings: The attempt to examine both life events throughout the life course and family history over generations was found to be an effective way to understand a service user and his/her family and then support recovery. The cases where even people with severe and persistent mental health problems have successfully achieved full recovery have been accumulated. Research limitations/implications: The limitations of the approach in the context of Japanese mental health services, and the necessity of additional evidence are acknowledged and some thoughts shall be given to future development. Originality/value: Seikatsu Rinsho approach can provide a new angle to understand service users and family and a new way to support recovery.